Combining experiential knowledge with scholarship in charting the decline of the National Health Service in England - Scambler, Graham (Frontiers in Sociology, 2023)
The sustained governmental assault on the National Health Service (NHS) in England during post-1970s financialised or rentier capitalism has received considerable attention by the research community. There is some evidence, however, that many of those members of the public who have not had occasion to use the NHS remain largely ill-informed about the extent of, and reasons for, its present troubles. In this paper I offer an auto/biographic account of my own recent experiences as a patient with type 2 diabetes and subsequent polymyalgia in both primary and secondary care. I then deploy analytic induction to consider, and explain, my personal travails against the background of the shifting nature of doctor-patient interaction occasioned by governmental politics in relation to the NHS. The result is an illustrated story of the decline of health care at a political juncture when the ever-expanding capital assets of a tiny minority of the population trumps the health care needs of the population as a whole. The present impoverishment of management and care must be understood with reference to wider aspects of macro-social change. The paper concludes with some ideas about how to (re)fund a severely ailing NHS.